Educational management in a digital age: boss phubbing and teacher motivation - Erdem, Mukadder; Kaya, Esra (Institute of Advanced Engineering and Science, 2025)
The study aims to assess the level of phubbing behavior an antisocial common mobile phone using behavior of school principals and how it affects the motivation of the teachers working at Anatolian High Schools and Vocational High Schools. This relational screening modelled study was conducted in these schools in the 2nd term in 2022 to 2023 school year. For data collection purposes, Boss Phubbing Scale and Multidimensional Work Motivation Scale were used and 268 answers were collected from the whole population. The data was analyzed through descriptive statistics, exploratory factor analysis (EFA), Cronbach’s alpha reliability analysis, one-way analysis of variance (ANOVA), unpaired t test, Pearson correlation analysis and regression analysis. The data derived from these analyses indicates that while school principals phub teachers at a low level and their boss phubbing scores differentiate in accordance with the work experience of teachers; teachers’ motivation is high and there is a significant and positive relationship between boss phubbing of school principals and two factors of Multidimensional Work Motivation Scale, which were extrinsic motivation and amotivation. It may be suggested that school principals should alter their boss phubbing behavior or modify it to make the best of it.